2019
DOI: 10.1038/s41598-019-38711-7
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin and its metabolite isorhamnetin promote glucose uptake through different signalling pathways in myotubes

Abstract: Quercetin and its metabolite isorhamnetin elicit various beneficial effects on human health. However, their bioavailability is low. In this study, we investigated whether low concentrations in the physiological range could promote glucose uptake in L6 myotubes, as well as the underlying molecular mechanisms. We found that 0.1 nM and 1 nM quercetin or 1 nM isorhamnetin significantly increased glucose uptake via translocation of glucose transporter type 4 (GLUT4) to the plasma membrane of L6 myotubes. Quercetin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 58 publications
(81 reference statements)
4
62
0
Order By: Relevance
“…In recent years, studies indicated that 1 µM propolis extract significantly promoted GLUT4 translocation and glucose uptake (Ueda, Hayashibara, & Ashida, ). The presence of 0.1 nM and 1 nM quercetin, or 1 nM isorhamnetin significantly increased glucose uptake by GLUT4 (Jiang, Yamashita, Nakamura, Croft, & Ashida, ). This study found that the insulin receptor substrate in the CGA‐treated group was not activated, and did not promote the expression of GLUT4.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies indicated that 1 µM propolis extract significantly promoted GLUT4 translocation and glucose uptake (Ueda, Hayashibara, & Ashida, ). The presence of 0.1 nM and 1 nM quercetin, or 1 nM isorhamnetin significantly increased glucose uptake by GLUT4 (Jiang, Yamashita, Nakamura, Croft, & Ashida, ). This study found that the insulin receptor substrate in the CGA‐treated group was not activated, and did not promote the expression of GLUT4.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, glucose transporter 4 (GLUT4) induction through insulin-stimulated PI3K/AKT has an important role in whole-body glucose homeostasis by glucose intake at adipose tissue, cardiomyocytes and skeletal muscle cells ( Klip, McGraw & James, 2019 ). Previous reports on flavonoids like apigenin (TP5), quercetin (TP14), kaempferol showed enhancement in GLUT4 translocation ( Alkhalidy et al, 2015 ; Hossain et al, 2014 ; Jiang et al, 2019 ). According to the findings of our study, apigenin (TP5), luteolin (TP13), and quercetin (TP14) showed interaction with the target GLUT4 ( Table S5 ).…”
Section: Discussionmentioning
confidence: 90%
“…These findings indicated that insulin-like activity of T. polium is a result of increase in GLUT4 translocation ( Kadan et al, 2018 ). Quercetin (TP14) and gallic acid (TP16) increased glucose uptake through IRS1/PI3K/AKT signaling ( Gandhi et al, 2014 ; Jiang et al, 2019 ). Furthermore, it was shown that gallic acid and p -coumaric acid (TP17) ameliorate insulin shortage and insulin resistance ( Abdel-Moneim et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, glucose transporter 4 (GLUT4) induction through insulin-stimulated PI3K/AKT has an important role in whole-body glucose homeostasis by glucose intake at adipose tissue, cardiomyocytes and skeletal muscle cells (Klip et al 2019). Previous reports on flavonoids like apigenin (TP5), quercetin (TP14), kaempferol showed enhancement in GLUT4 translocation (Alkhalidy et al 2015;Hossain et al 2014;Jiang et al 2019). According to the findings of our study, apigenin (TP5), luteolin (TP13), and quercetin (TP14) showed interaction with the target GLUT4 (Table S5).…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicated that insulin-like activity of T. polium is a result of increase in GLUT4 translocation (Kadan et al 2018). Quercetin (TP14) and gallic acid (TP16) increased glucose uptake through IRS1/PI3K/AKT signaling (Gandhi et al 2014;Jiang et al 2019). Furthermore, it was shown that gallic acid and p-coumaric acid (TP17) ameliorate insulin shortage and insulin resistance (Abdel-Moneim et al 2018).…”
Section: Discussionmentioning
confidence: 99%